Personalities, sequences of strategies and actions, and game attacks: A statistical discourse analysis of strategic board game play. (August 2022) - Shih, Ju-Ling; Chiu, Ming Ming; Lin, Chang-Hsin
Abstract: During a game, personalities and recent interaction sequences of strategies or actions can affect the likelihood of a specific game action (e.g., attack). Seventeen players played eight face-to-face, educational games (four players per game) and spoke for 8432 turns, all video recorded. A mobile game system collected their game actions. Statistical discourse analysis showed that compared to other variables, the following were less likely to yield an attack: extrovert player, exactly one extrovert in a game, lie, neutral talk, plan, threaten, criticize, pity, altruistic actions, deceive, or move. By contrast, the following were more likely to yield an attack: exactly two extrovert players, one pace/patient player, an attack in the previous turn, or an attack or criticism two turns ago. Also, consecutive attacks sharply raised the likelihood of an immediate attack. Mediation tests showed that an extrovert was more likely to plan or criticize, resulting in fewer attacks. Close examination of the transcripts showed that two extroverts will goad others to attack, and that different gaming goals (e.g., complete task, weaken opponent, revenge) motivated attacks. Together, these results show why and how players attack by identifying factors that affect the likelihood of an attack: a player's personality, personalities within a game, game actions, and group dynamics. These results inform our understanding of aggression within a framework of complex, dynamic gaming strategies and behaviors during interactive games for educational purposes. Highlights: Statistical discourse analysis of 8432 utterances by 17 people in 8 games. An extrovert was less likely than other players to attack. In games with two extroverts, they goaded other players to attack. After attacks in the previous turn or two turns ago, an attack was more likely. An attack was less likely with: lie, neutral talk, plan, threaten, criticize, pity, altruistic actions, deceive, or move.